Combining physical and psychosocial safety: A comprehensive workplace safety model. (December 2020) - Yaris, Cat; Ditchburn, Graeme; Curtis, Guy J.; Brook, Libby
Highlights: Physical and psychosocial safety need a comprehensive approach in the literature. Organizations create policy and practice addressing physical and psychosocial safety. The introduced model aims to fill the gap through a comprehensive approach. The utility behind an integrative approach benefits research and organizations. Abstract: The majority of workplace safety models focus solely on physical elements of safety. Evidence in the literature suggests the need for psychosocial safety to be considered in conjunction with physical safety. Previous models have identified certain job demands and resources as valuable indicators of safety behavior. This paper focuses on developing a comprehensive approach to workplace safety through a proposed physical and psychosocial workplace safety (PPWS) model, where self-regulatory processes mediate the relationship of job demands and resources to safety behaviors. The aim is to provide a parsimonious, comprehensive approach to safety by summarizing and strengthening current theoretical explanations. The PPWS provides multiple contributions to the literature; 1) clear definitions and distinctions between variable conceptualization, 2) expands job demands and resources, 3) integrates physical and psychosocial safety, 4) provides a generalizable approach across multiple industries, 5) considers self-regulatory processes as mediators of safety behavior. These contributions provide benefits and opportunities for practitioners and academics.